A Randomized Phase I Bioequivalence Clinical Trial of a Paediatric Fixed-Dose Combination Antiretroviral Reconstitutable Suspension in Healthy Adult Volunteers. Issue 2 (February 2013) - Esseku, Fredrick; Joshi, Anjali; Oyegbile, Yemisi; Edowhorhu, Grace; Gbadero, Daniel; Adeyeye, Moji
Background: This study aimed to test the hypothesis that paediatric fixed-dose combination granule for reconstitution (comprising lamivudine/zidovudine/nevirapine 30/60/50 mg per 5 ml) as a test product is bioequivalent to the coadministered single entities of the reference products. Fixed-dose combination antiretroviral therapy provides adequate suppression of HIV-1 replication, provides barrier to the development of resistance, simplifies dosage regimen and improves adherence. Methods: An open label, randomized, two-way crossover study was conducted on 24 healthy adults under fasted conditions, with a washout period of 14 days between treatments. A total of 15 blood samples were collected before dosing and up to 96 h post dosing. The drugs were extracted from plasma and analysed using a validated high performance liquid chromatography - ultraviolet method. Non-compartmental pharmacokinetic (PK) analysis was performed to obtain the PK parameters, maximum plasma concentration (Cmax ), area under curve of plasma concentration–time curves from time zero to last measurable concentration (AUC0–t ) and area under curve extrapolated to infinity (AUC0–∞ ). ANOVA test was performed to determine the effect of model factors on the PK parameters. The two one-sided t-tests were performed on the log-transformed data to determine the 90% CI for the ratio of test to reference PK parameters. Results: The drugs were well tolerated and safe, with minimal adverse events. The ANOVA test indicated the absence of any significant effects ( P >0.05) due to the model parameters. The 90% CI for the geometric mean ratio of test/ reference for Cmax, AUC0–t and AUC0–∞ for lamivudine, zidovudine and nevirapine were within the 80–125% bioequivalence limits. Conclusions: This single-dose randomized study found that the test and reference products met the criteria for bioequivalence in the fasting healthy adult volunteers.